2018
DOI: 10.1021/acs.jpcc.8b08787
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathiafulvalene Scaffold-Based Sensitizer on Hierarchical Porous TiO2: Efficient Light-Harvesting Material for Hydrogen Production

Abstract: In this work, a photochemical device that contains thioalkyl-substituted tetrathiafulvalene dyes and hierarchical porous TiO2 has been designed and successfully employed in visible light-driven hydrogen production. The design strategy boosts up the desirable photophysical properties of catalysts and is well supported by optical, electrochemical, and computational studies. The introduction of thioalkyl-substituted tetrathiafulvalene dyes as light-harvesting sensitizers onto the porous TiO2 triggers unprecedente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The fitted τ1 lifetimes of G1 and G3 were almost the same (0.11 and 0.12 ns), however the τ2 lifetime of G3 (1.75 ns) was longer than that of G1 (1.24 ns), which corresponded to the lower charge recombination as well as higher photo activity in H 2 evolution. The optimized DSP of G3 achieved a remarkable H 2 yield of 123 mmol g −1 under irradiation (>500 nm) after 5 h, and a high AQY of 40.87 % was obtained under 450 nm monochrome light [72] …”
Section: Improved Photosensitizers – D‐π‐a Dyesmentioning
confidence: 98%
See 1 more Smart Citation
“…The fitted τ1 lifetimes of G1 and G3 were almost the same (0.11 and 0.12 ns), however the τ2 lifetime of G3 (1.75 ns) was longer than that of G1 (1.24 ns), which corresponded to the lower charge recombination as well as higher photo activity in H 2 evolution. The optimized DSP of G3 achieved a remarkable H 2 yield of 123 mmol g −1 under irradiation (>500 nm) after 5 h, and a high AQY of 40.87 % was obtained under 450 nm monochrome light [72] …”
Section: Improved Photosensitizers – D‐π‐a Dyesmentioning
confidence: 98%
“…The optimized DSP of G3 achieved a remarkable H 2 yield of 123 mmol g À 1 under irradiation (> 500 nm) after 5 h, and a high AQY of 40.87 % was obtained under 450 nm monochrome light. [72] Besides being as π-spacer mentioned above, DPP group could also be involved as donor moiety due to its well-established synthesis, adjustable photophysical properties and high performances as already reported in optoelectronic devices such as organic transistors and organic and hybrid solar cells. [73] Julien Warnan et al reported the first example of a series of DPP dyes with a terminal phosphonic acid group, bearing different side-chains and electronically active substituents (Figure 35 and Table 1, No.…”
Section: Other Dyes Based On Novel Donorsmentioning
confidence: 99%
“…Splitting water into hydrogen and oxygen by photocatalysts is recognized as one of the promising strategies to utilize and store the inexhaustible solar energy . Dye sensitized titanium dioxide (TiO 2 ) and wide band gap metal oxides are widely used as photocatalysts because of the abundance of both organic dyes and metal oxides and the tunable energy level alignments between them, which enables the combination of efficient solar energy harvesting and charge separation capability . The minimum theoretical energy threshold for water splitting is 1.23 eV, but the energy of the photons used for this process is typically larger than 2.0 eV as a result of a number of energy‐loss processes including the reorganization of the excited state of the photocatalyst system, overpotential of half reactions, and the energy lost in the charge‐transfer (redox) processes.…”
Section: Figurementioning
confidence: 99%
“…Different types of photoactive compounds can be included in the design of a dye with specific structure: some D-A-π-A perylene dyes, featuring cyanoacrylic acid and dicyanomethylene rhodamine as the acceptor/anchoring group, combined with a N-annulated perylene donor and a quinoxaline auxiliary acceptor [63]; two triphenylamine-benzimidazole-based dyes bound on TiO 2 , with Cu 2 WS 4 nanocubes as an alternative water splitting co-catalyst to Pt [64]; a particular composite dye, consisting of π-conjugated indoline-rhodanine with a chlorophyll derivative, which induced panchromatic absorption in the visible range, efficient electron transfer, and prolonged stability [65]; a series of dyes with triphenylamine donor, vinyltiophene bridge, and a cationic pyridinium acceptor (cationic D-π-A photosensitizers) [66]. A superior H 2 evolution rate was recently reached with a thioalkyl-substituted tetrathiafulvalene dye on mesoporous TiO 2 [67].…”
Section: Organic Dye-sensitized Tiomentioning
confidence: 99%